A description of recent drought prevalence in the Limpopo River Basin - Ghosh, Surajit; Vigneswaran, Kayathri; Dickens, Chris; Retief, H.; Garcia Andarcia, Mariangel (International Water Management Institute, 2024)
This report provides an in-depth analysis of drought conditions in the Limpopo River Basin (LRB), with a focus on drought frequency, meteorological patterns, and agricultural impacts. Historical drought data and earth observation (EO) datasets are used to monitor and forecast drought severity. Key indices such as the Standardized Precipitation Index (SPI), Vegetation Condition Index (VCI), and rainfall anomalies derived from advanced EO technologies offer valuable insights into the basin's drought dynamics.